The emergence of value chain thinking - Simatupang T. (2017)
© Copyright 2017 Inderscience Enterprises Ltd. The concept value chain has been promoted by Porter for more than three decades. A value chain represents a chain of activities that an organisation performs to deliver a valuable product for the market. Porter's value chain assumes that an organisation is a system composed of inputs, transformation processes, and outputs. Each activity in the system involves the acquisition and consumption of resources. How the organisation carries out value chain activities determines costs and profits. One enhances the competitiveness of a company by improving its value chain structure. However, little attention has been given to developing value chain thinking. This paper examines the emergence of value chain thinking and proposes new value chain thinking that involves a chain of activities linked to one another in order to sustain value. A conceptual model is presented which consists of four steps: value discovery, value design, value delivery, and value capture. A methodology is also proposed in which to operationalise the value chain thinking.